The Analysis Of Figurative Meaning Of The Lyrics The House Of Wolves And Sleepwalking By Bring Me The Horizon Band - Sastra Wibawa, I Nyoman Aditya (Humanis; Volume 16. No. 1. Juli 2016, 2017)
In general, symbols are the richest and at the same time also the most difficult poetical figures. A complex natural symbolism runs through the poem, used by the poet to present complex psychological truths in an essay. This symbolism has been differently interpreted by different critics. This study which is concerned with the symbolic meaning found in the lyrics in Bring Me the Horizon album Sempiternal is aimed to show hidden meanings through his simple words and to fulfill our inquiries of what exactly the symbolic meanings on this poem by interpreting those words supported by his background and how it is constructed in the poem. The data were taken from lyrics written by Bring Me the Horizon (2013), sempiternal . The lyrics itself was taken from the album written by Bring Me the Horizon entitled Sempiternal .Thedocumentary method was used to collect data, The data were analyzed through reading, classifying, collecting and including extent information about the poet. In analyzing data, qualitative and descriptive methods were applied. In this study, the main theory applied is the theory proposed by Knickerbocker (1963:368) while others are supporting theories. The results of the study show that the use of symbol such as through intrinsic approach and figurative language to make a lyricmore beautiful and to express the poet's imagination and ideas indirectly. Through the use of symbols the poet can be considered successful in making the lyric as an effective media to attain both the entertaining and teaching purposes.
Keywords: Symbolic meaning, Figurative meaning